2020
DOI: 10.3928/00220124-20191217-08
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Nurses' Arrhythmia Knowledge: Defining Competency

Abstract: Background: Most methods of evaluating arrhythmia knowledge acquisition are internally developed by nursing professional development practitioners and are institution specific. This approach has resulted in assessing nurses' minimal qualifications for rhythm recognition as defined by the facility but does not result in describing basic, intermediate, and advanced competency levels for practice. Method: This quantitative study with a convenience sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Given that most of the nurses in this study had completed BLS (63.9%) or ACLS (48.6%) courses, it is not surprising they can identify the asystole rhythm correctly and know how it should be managed. This finding is congruent with other studies [ 29 , 38 , 40 ]. In addition, the current study found nurses had difficulties identifying atrial flutter (58.4%), atrial fibrillation (50.2%), and third-degree complete heart block (56.9%).…”
Section: Discussionsupporting
confidence: 94%
“…Given that most of the nurses in this study had completed BLS (63.9%) or ACLS (48.6%) courses, it is not surprising they can identify the asystole rhythm correctly and know how it should be managed. This finding is congruent with other studies [ 29 , 38 , 40 ]. In addition, the current study found nurses had difficulties identifying atrial flutter (58.4%), atrial fibrillation (50.2%), and third-degree complete heart block (56.9%).…”
Section: Discussionsupporting
confidence: 94%
“…Cross‐sectional descriptive studies reported varying levels of nurses’ knowledge of ECG interpretation. For example, one quantitative study that looked at arrhythmia recognition competency for acute care nurses showed that 96% of nurses correctly identified atrial fibrillation and 95% ventricular tachycardia (Keller et al, 2020). By comparison, 71% of ambulance nurses in a prospective quantitative survey correctly identified atrial fibrillation and 35% ventricular tachycardia (Werner et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A positive relationship was demonstrated between professional factors (exposure, confidence, comfort or perception) and competency in ECG interpretation. Two quantitative studies reported the amount of exposure to ECG interpretation directly related to nurses’ abilities to interpret ECGs (Keller et al, 2020; VanArsdale, 1998). One qualitative study discussed ‘Use it or lose it’, illustrating the importance of nurses’ continued exposure to ECG interpretation (Nickasch, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations